Clinicians' gut feeling about serious infections in children: observational study. (25th September 2012) - Van den Bruel, Ann; Thompson, Matthew; Buntinx, Frank; Mant, David
Abstract : Objective To investigate the basis and added value of clinicians' "gut feeling" that infections in children are more serious than suggested by clinical assessment. Design Observational study. Setting Primary care setting, Flanders, Belgium. Participants Consecutive series of 3890 children and young people aged 0-16 years presenting in primary care. Main outcome measures Presenting features, clinical assessment, doctors' intuitive response at first contact with children in primary care, and any subsequent diagnosis of serious infection determined from hospital records. Results Of the 3369 children and young people assessed clinically as having a non-severe illness, six (0.2%) were subsequently admitted to hospital with a serious infection. Intuition that something was wrong despite the clinical assessment of non-severe illness substantially increased the risk of serious illness (likelihood ratio 25.5, 95% confidence interval 7.9 to 82.0) and acting on this gut feeling had the potential to prevent two of the six cases being missed (33%, 95% confidence interval 4.0% to 100%) at a cost of 44 false alarms (1.3%, 95% confidence interval 0.95% to 1.75%). The clinical features most strongly associated with gut feeling were the children's overall response (drowsiness, no laughing), abnormal breathing, weight loss, and convulsions. The strongest contextual factor was the parents' concern that the illness was different from their previous experience (odds ratio 36.3, 95% confidence interval 12.3 to 107). Conclusions A gut feeling about the seriousness of illness in children is an instinctive response by clinicians to the concerns of the parents and the appearance of the children. It should trigger action such as seeking a second opinion or further investigations. The observed association between intuition and clinical markers of serious infection means that by reflecting on the genesis of their gut feeling, clinicians should be able to hone their clinical skills.